2002
DOI: 10.1177/008124630203200107
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Complaints and Disciplinary Action against South African Psychologists

Abstract: This study investigated the scope and nature of complaints, related to unethical behaviour, that have been lodged against South African psychologists with the Health Professions Council of South Africa (HPCSA) between 1990 and 1999. Certain biographical characteristics of the complainants and their accused also received attention. During this period, complaints were lodged annually against approximately 1% of South African psychologists, of which approximately 15% resulted indisciplinary inquiries. Only 5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In our study, mental health practitioners had three times the risk of complaint regarding sexual boundary breaches compared with physical health practitioners. High rates of concern about sexual misconduct by psychiatrists and psychologists are a consistent finding in previous studies of complaints,11 regulatory actions6 10 12 and self-reported behaviour 7 37. Compared with comparator professions in this study, the day-to-day practice of mental health practitioners more often involves being alone with patients behind closed doors, discussing more personally-intimate information, for longer periods of time.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, mental health practitioners had three times the risk of complaint regarding sexual boundary breaches compared with physical health practitioners. High rates of concern about sexual misconduct by psychiatrists and psychologists are a consistent finding in previous studies of complaints,11 regulatory actions6 10 12 and self-reported behaviour 7 37. Compared with comparator professions in this study, the day-to-day practice of mental health practitioners more often involves being alone with patients behind closed doors, discussing more personally-intimate information, for longer periods of time.…”
Section: Discussionsupporting
confidence: 87%
“…Relative to other health professionals, psychiatrists and psychologists have been shown to have high rates of complaints and disciplinary actions 1–5. Prominent issues include sexual boundary violations,6–14 concerns about practitioners’ involvement in legal proceedings or reports,11 15–17 and breaches of confidentiality 9 17…”
Section: Introductionmentioning
confidence: 99%
“…Although the HPCSA accredits all CPD providers, often these courses are presented by unqualified individuals and not ethics educators with proven in-depth knowledge of moral reasoning and global ethics principles. Although Scherrer et al (2002) caution that the relationship between ethics training and ethical behaviour is complex and not necessarily linear, which we fully support, it is also strongly recommended that thorough, in-depth training in ethics, including bioethics and professional integrity, must form an integral and compulsory part of any undergraduate and postgraduate psychology programme by experienced ethics educators. Although more than 10 years have elapsed since Scherrer et al (2002) argued that inadequate training in ethics seems to be the proverbial root cause of the evil in many cases of ethics misconduct, it remains worrisome that the HPCSA in almost all cases opted to only impose financial and/ or suspended suspension period penalties without requiring any form of additional ethical awareness training for the transgressors.…”
Section: Conclusion and Recommendationsmentioning
confidence: 88%
“…Although Scherrer et al (2002) caution that the relationship between ethics training and ethical behaviour is complex and not necessarily linear, which we fully support, it is also strongly recommended that thorough, in-depth training in ethics, including bioethics and professional integrity, must form an integral and compulsory part of any undergraduate and postgraduate psychology programme by experienced ethics educators. Although more than 10 years have elapsed since Scherrer et al (2002) argued that inadequate training in ethics seems to be the proverbial root cause of the evil in many cases of ethics misconduct, it remains worrisome that the HPCSA in almost all cases opted to only impose financial and/ or suspended suspension period penalties without requiring any form of additional ethical awareness training for the transgressors. The implication is that ethical misconduct may increasingly be regarded by practitioners as merely a business/financial risk but not primarily as an ethics and integrity matter as indicated in the title of the relevant South African guide document (Government Gazette, 2006), namely, the 'Ethical rules of conduct for practitioners registered under the Health Professions Act' (emphasis added).…”
Section: Conclusion and Recommendationsmentioning
confidence: 88%
“…Despite the smorgasbord of ethical theories available to practitioners, the direst of unethical behaviours still occur within their ranks (see Scherrer, Louw, & Möller, 2002 for a recent review). Often, abstract, 'universal' ethical principles codified in professional legislation have little relevance for moral agents who have to make tough judgement calls.…”
Section: The Nature Of the Problemmentioning
confidence: 99%